Experimental studies of screw drill with frozen soil interaction - M. I. Zenin; S. I. Ivanov (Вестник СибАДИ, 2024)
Introduction. The process of formation of wells in frozen soils is one of the complex processes of excavation. A drilling tool of a new geometric shape forms a well by brittle destruction of the rock. The purpose of the conducted experimental studies was to determine the effect on the energy intensity of the drilling process and on the well diameter coefficient of the angle of rotation of the radius of the screw blade, at which its increment occurs on the destructive part and the angle of inclination of the forming upper surface of the screw blade to the axis of rotation.Materials and methods. The article describes a methodology for conducting laboratory experiments to study the interaction of a drilling tool of a new geometric shape with frozen soils. The ranges of values of the studied factors are determined. The matrix of the complete factorial experiment is constructed.Results. As a result of laboratory experiments, the influence of the geometric parameters of the drilling tool on the energy intensity of the drilling process and on the well diameter coefficient was determined. The dependencies of the torque and the well diameter coefficient on the angle of rotation of the radius of the helical blade, at which its increment occurs on the destructive part, the angle of inclination of the forming upper surface of the helical blade to the axis of rotation and the angle of elevation of the middle helical line of the helical blade are established.Discussions and conclusion. It is established that the drilling tool carries out the formation of a well due to the brittle destruction of the well, which makes it possible to achieve more efficient drilling. And also the dependences of the rational values of the investigated geometric parameters of the drilling tool of a new geometric shape are determined.